2021
DOI: 10.4018/ijitsa.290004
|View full text |Cite
|
Sign up to set email alerts
|

Grey Wolf-Based Linear Regression Model for Rainfall Prediction

Abstract: This paper develops a rainfall prediction technique, named GWO-based Linear Regression (GWLR) model, using the linear regression model and Grey Wolf Optimizer (GWO). The linear regression model is used to predict the value of a dependent variable from an independent variable on the basis of regression coefficient. The proposed GWLR predicts rainfall based on the input time-series weather data using the proposed GWLR model, in which the regression coefficients are obtained optimally using the GWO. Thus, the rai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Second, by using the MSE as an evaluation metric, the MSE of GWO is 20.54, and the MSE for Firefly, GA, PSO, ZOA, PDO, WSO, and MFO models are 47. 74 Sixth, the R 2 as an evaluation metric is used to measure the extent of the relationship between the independent variable and the dependent variable. It can be observed that GWO has the highest value among all other models.…”
Section: B Experimental Results For the Cocomo Model I On The Nasa18 ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Second, by using the MSE as an evaluation metric, the MSE of GWO is 20.54, and the MSE for Firefly, GA, PSO, ZOA, PDO, WSO, and MFO models are 47. 74 Sixth, the R 2 as an evaluation metric is used to measure the extent of the relationship between the independent variable and the dependent variable. It can be observed that GWO has the highest value among all other models.…”
Section: B Experimental Results For the Cocomo Model I On The Nasa18 ...mentioning
confidence: 99%
“…• Attacking the victim. The first reason is that the GWO has proven its efficiency in studies similar to the nature of our research problem, such as in [74], where they proposed a model to predict rainfall based on the input time-series weather data using GWO in India, Jammu, and Kashmir. They used 4 datasets.…”
Section: The Meta-heuristic Algorithms a Grey Wolf Optimization Algor...mentioning
confidence: 99%
“…The correlation is reflected in the fact that precipitation acts as a common source of recharge for both surface water and groundwater, while the source of recharge for precipitation comes from evaporation, the same discharge method for both surface water and groundwater, thus bringing the 'three waters' into the same cyclic relationship. The constraint system is that there are checks and balances on the amount and timing of transformations between the three waters [15][16].…”
Section: The "Three Waters" Conversion Relationship In a River Basinmentioning
confidence: 99%
“…Artificial Intelligence (AI) is rapidly transforming our world. With time it has spread into many business areas [1][2][3] and is originating in medical field too with the increase in the complication and evolution of data in biological sciences, AI is gradually being applied within the field. The AI technologies such as machine learning (ML) and deep learning (DL) [4][5][6][7] have played a foremost role in the detection and prediction of diseases [8,9] either by means of the disease symptom datasets [10,11] or medical image datasets, which have helped the doctors in a positive way.…”
Section: Introductionmentioning
confidence: 99%